Positive and Useful Voices in Patients With Schizophrenia: Prevalence, Course, Characteristics, and Correlates. Issue 8 (August 2020) - Lorente-Rovira, Esther; Grasa, Eva; Ochoa, Susana; Corripio, Iluminada; Peláez, Trinidad; López-Carrillero, Raquel; Morano-Guillén, María; Gutiérrez-Gea, Ángela; Villagrán, José M.; Llácer, Blanca; Sanjuán, Julio
Abstract : Abstract: Auditory verbal hallucinations (AVHs) in schizophrenia have been characterized by their negative emotional valence. However, positive hallucinations have also been described. The objective of the current study is to explore the prevalence, course, characteristics, and associations of positive and useful voices. The Positive and Useful Voices Inquiry and some clinical and functioning instruments were administered to a sample of 68 patients with schizophrenia or schizoaffective disorder presenting with AVHs. Both the lifetime and current prevalences of positive and useful voices were high. Although AVHs tended to remain stable, there was a trend to decrease over time. The strongest positive attributions of such voices were that they help patients to feel important, amuse them, and help them to conduct their studies and carry out their profession. They seem to be mainly related to more grandiosity and to worse general functioning. Interference with biological and psychological treatments and the need for personalized formulations in patients with auditory hallucinations are discussed. Abstract : Supplemental digital content is available in the text.